Development of Teaching Materials on Sine and Cosine Rules based on Flipbook for Mathematics Education Students - Anggy Heriyanti; Nurjannah Nurjannah; Andi Baso Kaswar; A. Mutahharah Mutahharah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
The purpose of this research is to produce a product in the form of a teaching material as a medium in studying the sine and cosine rule material. This study was development research that was designed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. To obtain valid and effective teaching materials, the validity of the research instrument was tested and the validity of the developed teaching materials was tested. The teaching materials that have been implemented are then assessed by the research subjects to determine their effectiveness. The results obtained are: flipbook-based teaching materials on the sine and cosine rule materials are declared to meet the validity and effectiveness. These results were obtained after being tested for validity by experts which consisted of validating teaching materials in the form of teaching materials and problem-solving questions, all of which were in the very valid category, namely 3.76. Meanwhile, for display validation, it is in the very valid category with the average validator value of 3.56. Teaching materials are declared practical based on the results of the analysis, there are 97.1% of respondents who rate the attractiveness of teaching materials, 88.6% of respondents who assess interest/motivation, 89.4% of respondents who rate ease of use, and 95.7% respondents who assess the functioning of teaching materials. Teaching materials are declared effective based on the results of the analysis, there are 96.3% of respondents who rate the material, 87.6% of respondents who rate problem solving, and 90.9% of respondents who rate visual communication.